ADVANCING GREEN MARKETING THROUGH GLOBAL CHALLENGES AND NEW HORIZONS (Marketing Jurnali, 2025)
Green marketing has emerged as a critical strategic domain as organizations increasingly integrate environmental sustainability into business operations. This paper examines the contemporary challenges confronting global green marketing, including greenwashing, regulatory heterogeneity, limited measurement standards, and the persistent disparity between consumer attitudes and actual behavior. Drawing on theoretical frameworks such as the Theory of Planned Behavior, Resource Based View, and Institutional Theory, the study evaluates emerging strategies including technologyenabled transparency, circular economy integration, consumer co-creation, and crosscultural adaptation. Evidence-based recommendations are provided for enhancing credibility, operational efficiency, and consumer engagement. The analysis underscores the need for rigorous longitudinal research to inform sustainable marketing practice and policy formulation.